Geophysical Survey at Morgantina - Kay, Stephen; Trümper, Monika; Heinzelmann, Michael; Pomar, Elena (Archäologischer Anzeiger, 2020)
Geophysical surveys were conducted at Morgantina in 1970, 2012 and 2018, with the objective of better understanding the city plan of the Archaic city on the Cittadella Hill and the Classical and Hellenistic city on the Serra Orlando Ridge. This paper focuses on the results of the 2018 survey conducted over three sectors on the Serra Orlando Ridge. It demonstrates that magnetometry was successful in rapidly recording subsurface archaeological features across the site, including the presence of streets, walls and areas of habitation. The general layout of streets and insulae of the orthogonal grid plan that was established in the mid-5th century B.C. on the Serra Orlando Ridge has been confirmed and the precise course of streets has been defined in more detail than hitherto known.